Bibliometric Analysis of Education Budget Management and School Infrastructure Quality in Disadvantaged Areas - Loso Judijanto; Nanny Mayasari; Yana Priyana (West Science Interdisciplinary Studies, 2024)
This study presents a bibliometric analysis of research focused on education budget management and school infrastructure quality in disadvantaged areas from 2000 to 2024. The analysis explores key themes such as financial management, infrastructure development, and the role of technology in enhancing educational outcomes. Results reveal that effective budget management and strategic resource allocation are pivotal in improving school facilities and overall educational quality, particularly in under-resourced regions. The integration of technology, accelerated by the COVID-19 pandemic, offers promising solutions for bridging gaps in access and learning quality, although the digital divide remains a significant challenge. Furthermore, strong leadership and community involvement are identified as crucial for the successful implementation of educational reforms. This study underscores the importance of a holistic approach that combines financial management, infrastructural improvements, and technological integration to address educational disparities in disadvantaged areas.